a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
A(a(b(x1))) → B(a(a(a(x1))))
B(a(b(a(x1)))) → B(b(x1))
B(a(b(a(x1)))) → B(x1)
A(a(b(x1))) → A(x1)
B(a(b(a(x1)))) → A(b(b(x1)))
A(a(b(x1))) → A(a(x1))
A(a(b(x1))) → A(a(a(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
A(a(b(x1))) → B(a(a(a(x1))))
B(a(b(a(x1)))) → B(b(x1))
B(a(b(a(x1)))) → B(x1)
A(a(b(x1))) → A(x1)
B(a(b(a(x1)))) → A(b(b(x1)))
A(a(b(x1))) → A(a(x1))
A(a(b(x1))) → A(a(a(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
B(a(b(a(x1)))) → B(x1)
A(a(b(x1))) → A(x1)
A(a(b(x1))) → A(a(x1))
A(a(b(x1))) → A(a(a(x1)))
POL(A(x1)) = 1 + x1
POL(B(x1)) = 2 + x1
POL(a(x1)) = x1
POL(b(x1)) = 1 + x1
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(x1))) → B(a(a(a(x1))))
B(a(b(a(x1)))) → B(b(x1))
B(a(b(a(x1)))) → A(b(b(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
B(a(b(a(x1)))) → B(b(x1))
B(a(b(a(x1)))) → A(b(b(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
B(a(b(a(a(b(a(x0))))))) → B(a(b(b(x0))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
B(a(b(a(a(b(a(x0))))))) → B(a(b(b(x0))))
B(a(b(a(x1)))) → A(b(b(x1)))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
B(a(b(a(a(b(a(x0))))))) → A(b(a(b(b(x0)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
B(a(b(a(a(b(a(x0))))))) → B(a(b(b(x0))))
B(a(b(a(a(b(a(x0))))))) → A(b(a(b(b(x0)))))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
B(a(b(a(a(b(a(x0))))))) → B(a(b(b(x0))))
B(a(b(a(a(b(a(x0))))))) → A(b(a(b(b(x0)))))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
A(a(b(a(b(x0))))) → B(a(a(b(a(a(a(x0)))))))
A(a(b(b(x0)))) → B(a(b(a(a(a(x0))))))
B(a(b(a(a(b(a(x0))))))) → B(a(b(b(x0))))
B(a(b(a(a(b(a(x0))))))) → A(b(a(b(b(x0)))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
a(a(b(x))) → b(a(a(a(x))))
b(a(b(a(x)))) → a(b(b(x)))
A(a(b(a(b(x))))) → B(a(a(b(a(a(a(x)))))))
A(a(b(b(x)))) → B(a(b(a(a(a(x))))))
B(a(b(a(a(b(a(x))))))) → B(a(b(b(x))))
B(a(b(a(a(b(a(x))))))) → A(b(a(b(b(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
a(a(b(x))) → b(a(a(a(x))))
b(a(b(a(x)))) → a(b(b(x)))
A(a(b(a(b(x))))) → B(a(a(b(a(a(a(x)))))))
A(a(b(b(x)))) → B(a(b(a(a(a(x))))))
B(a(b(a(a(b(a(x))))))) → B(a(b(b(x))))
B(a(b(a(a(b(a(x))))))) → A(b(a(b(b(x)))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
a(a(b(x))) → b(a(a(a(x))))
b(a(b(a(x)))) → a(b(b(x)))
A(a(b(a(b(x))))) → B(a(a(b(a(a(a(x)))))))
A(a(b(b(x)))) → B(a(b(a(a(a(x))))))
B(a(b(a(a(b(a(x))))))) → B(a(b(b(x))))
B(a(b(a(a(b(a(x))))))) → A(b(a(b(b(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
a(a(b(x))) → b(a(a(a(x))))
b(a(b(a(x)))) → a(b(b(x)))
A(a(b(a(b(x))))) → B(a(a(b(a(a(a(x)))))))
A(a(b(b(x)))) → B(a(b(a(a(a(x))))))
B(a(b(a(a(b(a(x))))))) → B(a(b(b(x))))
B(a(b(a(a(b(a(x))))))) → A(b(a(b(b(x)))))
B1(b(a(A(x)))) → A1(b(a(B(x))))
B1(a(b(a(A(x))))) → A1(a(B(x)))
B1(b(a(A(x)))) → A1(a(b(a(B(x)))))
B1(b(a(A(x)))) → A1(a(a(b(a(B(x))))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(B(x))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(b(a(A(x)))) → A1(B(x))
B1(a(a(x))) → A1(a(b(x)))
A1(b(a(b(x)))) → A1(x)
B1(a(a(x))) → A1(b(x))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
A1(b(a(a(b(a(B(x))))))) → A1(b(A(x)))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
A1(b(a(a(b(a(B(x))))))) → B1(b(a(B(x))))
A1(b(a(a(b(a(B(x))))))) → B1(b(a(b(A(x)))))
B1(a(b(a(A(x))))) → A1(a(a(b(a(a(B(x)))))))
B1(b(a(A(x)))) → B1(a(B(x)))
A1(b(a(a(b(a(B(x))))))) → B1(a(b(A(x))))
A1(b(a(b(x)))) → B1(a(x))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
A1(b(a(a(b(a(B(x))))))) → B1(A(x))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(b(a(A(x)))) → A1(b(a(B(x))))
B1(a(b(a(A(x))))) → A1(a(B(x)))
B1(b(a(A(x)))) → A1(a(b(a(B(x)))))
B1(b(a(A(x)))) → A1(a(a(b(a(B(x))))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(B(x))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(b(a(A(x)))) → A1(B(x))
B1(a(a(x))) → A1(a(b(x)))
A1(b(a(b(x)))) → A1(x)
B1(a(a(x))) → A1(b(x))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
A1(b(a(a(b(a(B(x))))))) → A1(b(A(x)))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
A1(b(a(a(b(a(B(x))))))) → B1(b(a(B(x))))
A1(b(a(a(b(a(B(x))))))) → B1(b(a(b(A(x)))))
B1(a(b(a(A(x))))) → A1(a(a(b(a(a(B(x)))))))
B1(b(a(A(x)))) → B1(a(B(x)))
A1(b(a(a(b(a(B(x))))))) → B1(a(b(A(x))))
A1(b(a(b(x)))) → B1(a(x))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
A1(b(a(a(b(a(B(x))))))) → B1(A(x))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(b(a(A(x))))) → A1(a(a(b(a(a(B(x)))))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
A1(b(a(b(x)))) → A1(x)
B1(a(a(x))) → A1(a(b(x)))
A1(b(a(b(x)))) → B1(a(x))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
A1(b(a(b(x)))) → A1(x)
A1(b(a(b(x)))) → B1(a(x))
POL(A(x1)) = x1
POL(A1(x1)) = x1
POL(B(x1)) = 1 + 2·x1
POL(B1(x1)) = 1 + 2·x1
POL(a(x1)) = x1
POL(b(x1)) = 1 + 2·x1
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(a(a(b(a(a(B(x)))))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → A1(b(x))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(b(a(A(y0))))) → A1(a(a(a(a(a(b(B(y0))))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
B1(a(b(a(A(y0))))) → A1(a(a(a(a(a(b(B(y0))))))))
A1(b(a(b(x)))) → B1(b(a(x)))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
B1(a(b(a(A(x))))) → A1(a(b(a(a(B(x))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(b(a(A(y0))))) → A1(a(a(a(a(b(B(y0)))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(a(b(a(A(y0))))) → A1(a(a(a(a(b(B(y0)))))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → A1(b(x))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(b(a(A(x))))) → A1(b(a(a(B(x)))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(b(a(A(y0))))) → A1(a(a(a(b(B(y0))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → A1(b(x))
B1(a(a(x))) → B1(x)
B1(a(b(a(A(y0))))) → A1(a(a(a(b(B(y0))))))
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(a(b(x))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(a(b(b(a(b(A(x0)))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(a(b(b(a(B(x0))))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(b(a(A(x0)))))) → A1(a(a(a(a(a(b(a(B(x0)))))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(a(a(a(b(a(B(x0)))))))) → A1(a(b(b(a(b(A(x0)))))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(a(b(b(a(B(x0))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → A1(b(x))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
B1(a(a(b(a(A(x0)))))) → A1(a(a(a(a(a(b(a(B(x0)))))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → A1(a(b(x)))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(a(b(a(A(x0)))))) → A1(a(a(a(a(b(a(B(x0))))))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(b(b(a(B(x0)))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(b(b(a(b(A(x0))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(b(b(a(b(A(x0))))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → A1(b(x))
B1(a(a(b(a(A(x0)))))) → A1(a(a(a(a(b(a(B(x0))))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(a(a(b(a(B(x0)))))))) → A1(b(b(a(B(x0)))))
B1(a(a(x))) → B1(x)
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
A1(b(a(b(x)))) → B1(b(a(x)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
A1(b(a(b(b(a(a(b(a(B(x0)))))))))) → B1(b(b(b(a(b(A(x0)))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
A1(b(a(b(b(a(a(b(a(B(x0)))))))))) → B1(b(b(b(a(B(x0))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
A1(b(a(b(b(a(a(b(a(B(x0)))))))))) → B1(b(b(b(a(b(A(x0)))))))
B1(a(a(x))) → A1(b(x))
A1(b(a(b(b(a(a(b(a(B(x0)))))))))) → B1(b(b(b(a(B(x0))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → B1(x)
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(a(b(a(a(B(x0))))))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(a(a(b(a(A(y0))))))) → A1(a(a(a(a(a(a(a(a(b(B(y0)))))))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → A1(b(x))
B1(a(a(a(b(a(A(y0))))))) → A1(a(a(a(a(a(a(a(a(b(B(y0)))))))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(x))) → B1(x)
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(a(b(a(A(x0))))))) → A1(a(a(a(a(b(a(a(B(x0)))))))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
B1(a(a(a(b(a(A(y0))))))) → A1(a(a(a(a(a(a(a(b(B(y0))))))))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → A1(b(x))
B1(a(a(x))) → B1(x)
B1(a(a(a(b(a(A(y0))))))) → A1(a(a(a(a(a(a(a(b(B(y0))))))))))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
B1(a(a(a(a(x0))))) → A1(a(a(a(a(b(x0))))))
A1(b(a(b(b(a(A(x0))))))) → B1(a(a(a(b(a(a(B(x0))))))))
A1(b(a(b(a(x0))))) → B1(a(a(a(b(x0)))))
B1(a(a(a(b(x0))))) → A1(a(b(b(a(x0)))))
B1(a(a(a(a(x0))))) → A1(a(a(a(a(a(b(x0)))))))
B1(a(b(a(A(x))))) → B1(a(a(B(x))))
A1(b(a(b(b(a(b(x0))))))) → B1(b(b(b(a(x0)))))
B1(a(a(a(b(x0))))) → A1(b(b(a(x0))))
B1(a(a(x))) → B1(x)
B1(a(a(x))) → A1(b(x))
The value of delta used in the strict ordering is 1/4.
POL(A1(x1)) = 4 + (2)x_1
POL(B(x1)) = 4 + (9/4)x_1
POL(a(x1)) = 5/4 + x_1
POL(B1(x1)) = 7/4 + (3)x_1
POL(A(x1)) = 4 + (3/2)x_1
POL(b(x1)) = (3/2)x_1
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(a(a(x))) → a(a(a(b(x))))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QTRS Reverse
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
b(a(b(a(A(x))))) → a(a(a(b(a(a(B(x)))))))
b(b(a(A(x)))) → a(a(a(b(a(B(x))))))
a(b(a(a(b(a(B(x))))))) → b(b(a(B(x))))
a(b(a(a(b(a(B(x))))))) → b(b(a(b(A(x)))))
a(a(b(x1))) → b(a(a(a(x1))))
b(a(b(a(x1)))) → a(b(b(x1)))
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
b(a(a(x))) → a(a(a(b(x))))
a(b(a(b(x)))) → b(b(a(x)))